Key Success Factors of Online Food Ordering Services in Indore City: Exploring the Factors for Success in Online Food Ordering Services (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Food Industry has always been a profitable industry not only for manufacturers but also for the users and distributors. The online food delivery system is the need of an hour because of the recent changes in the industry and the increasing use of the internet. The foundation of study was based on both primary as well as secondary data. For primary data collection the survey was conducted for a purposeful analysis of the study on around 168 respondents. The research is concentrated on study and analysis of data collected from all those users who are already using the online food delivery services. Factor analysis identified 5 key factors namely app quality, service quality, social influence, food quality and promotion which are important for success of online food ordering services. Further, t test was applied to find out the factor which have significant impact on the success of online food ordering services.